The Social Dimension of Disability in the Theory of Economics - Garbat, Marcin (Studia Oeconomica Posnaniensia, 2017)
The author analyses the historical evolution of disability as a social problem and the institutional forms of solving it. The author, based on the social model of disability, discusses the role and place of not fully able people in selected economic theories and their impact on social policy. Disability is shown as a complex phenomenon, reflecting the structural features of society: characteristics of the economic an political system, the type of social relationships and cultural patterns. The author analyses how academic discussion on disability and theoretical models present in it translate into the philosophy of the system of support to the disabled, the form of the regulations and specific activities within it.